Cannabinoids use in adolescents and young adults with cancer: a single-center survey. Issue 4 (August 2020) - Podda, Marta; Pagani Bagliacca, Elena; Sironi, Giovanna; Veneroni, Laura; Silva, Matteo; Angi, Martina; Massimino, Maura; Ferrari, Andrea; Clerici, Carlo Alfredo
Objective: To present an investigation into the intake of cannabinoids in a population of adolescents and young adults with cancer. Methods: Sixty-six patients took part in the research: 27 reported having used cannabinoids, 21 before diagnosis; among the latter, 10 increased use during treatment. Results: Benefits were reported by 19% of responders regarding anxiety control, 24% for nausea, 29% for pain control and improvement of sleep, and 48% for appetite improvement. Conclusions: Cannabis use by patients may often be unknown to caregivers. Studying this subject may help to better define important therapeutic aspects of these substances.